2336. Adherence to Follow-up and CMV Testing in Infants Who Failed Newborn Hearing Screens: Evaluation of New Protocol to Ensure Follow-up and Testing - Penton, Manuel (Open Forum Infect Dis, 2019)
BACKGROUND: CMV is the most common non-hereditary cause of sensorineural hearing loss (SNHL) in children in the United States. SNHL may be the only presenting symptom in otherwise asymptomatic infants. Several states are making CMV testing mandatory for newborn infants who have a hearing deficit. Testing should be performed before 21 days of life to diagnose congenital CMV infection and provide effective therapy. However, the results of a retrospective 1 year audit of all newborn patients in the nursery of University Hospital of Brooklyn (UHB) who failed their hearing screen found that none were tested for CMV and approximately half failed to follow-up with audiology. Therefor we developed a new protocol to ensure testing and follow-up. METHODS: Under the new protocol, newborns who fail an initial and repeat hearing screen are tested for CMV in urine by culture and the audiology appointment is scheduled before discharge. Patients are tracked by a pediatric infectious disease fellow to ensure adherence to protocol. RESULTS: The pre-intervention audit conducted from November 1, 2017 to October 31, 2018 found 37/923 (4%) infants failed their hearing screening tests. Although 34/37 (92%) of these children had audiology appointments made before discharge, only 19 (56%) actually attended. Two (11%) children failed an otoacoustic emissions hearing test. One infant also went on to fail an auditory brainstem response test; both were lost to follow-up. None of these infants was tested for CMV. The new protocol was initiated November 1, 2018, 11/372 (3%) infants failed initial and repeat hearing screening tests. All 11 (100%) of these children had audiology appointments made before discharge, of which 9 (82%) attended. 2 (18%) of these children failed the otoacoustic emissions hearing test at that visit, 1 infant was lost to follow-up; 9 infants who failed hearing test were tested for CMV; 1 (9%) was positive. CONCLUSION: Although it has only been in place for 5 months, the new protocol has increased adherence to audiology appointments. CMV testing has increased from 0% to 82% and 1 patient has tested positive for congenital CMV infection. The ongoing success of this protocol could facilitate timely and appropriate treatment of CMV with valgancyclovir. [Image: see text] [Image: see text] DISCLOSURES: All authors: No reported disclosures.